SHORT AND LONG TERM ANALYSIS OF FOREIGN EXCHANGE RATES BASED ON INCOME LEVELS - Harunurrasyid, Harunurrasyid; Mardalena, Mardalena; Asngari, Imam; Rohima, Siti; Andaiyani, Sri (Journal of Economic Development, Environment and People, 2022)
The study aimed to determine the effect of foreign exchange demand and supply on exchange rates in four groups of countries based on per capita income levels from 1989-2018 using the ARDL panel method. The results showed remittances had a significant effect on exchange rates in panel A (low income countries), panel B (lower middle income countries), panel D (high income countries), while on panel C (upper middle income countries) remittances had no significant effect. Export and import variables have a significant effect on panels B, C, and D, and are not significant on panelS A. Meanwhile inflation variables have a significant effect on all types of panels.